Impact of the covid-19 pandemic on screen time of children and adolescents - Gonzaga,Diana (2022)
Abstract The use of screens by children and adolescents has been increasing in the last two decades, including mobile devices and interactive and social platforms. At present media exposure affects even young children and is part of their daily routine. Although there are benefits of media use for children, including educational potential, there are concerns about their overuse, especially in early childhood, during the crucial period of brain development. Data from national and international studies, reveal that COVID-19 pandemic- related restrictions, lockdowns and stay-at- home orders contributed to a remarkable increase in screen time (ST) in pediatric ages. The authors present a literature review on the repercussions of COVID-19 pandemics on the use of digital media, the associated risks and its impact on different health domains. Scientific evidence associates excessive use of digital media with physical, neurodevelopmental and mental adverse consequences. Excessive ST has been associated with obesity, sleep disturbance, language delay, impaired executive functions, general cognition and mental health, namely anxiety and depression. There are evidence-based recommendations to promote healthy screen habits for children and their families in order to mitigate the adverse effects of screen use. Increased ST in children and youth during the COVID-19 pandemic is a public health concern demanding policy-level interventions to promote accessible outdoor facilities for recreational and physical activities offering active and social alternatives to screens, to improve the mental and physical well-being of children and adolescents.